Editorial to the Special Issue: The global financial crisis – Analysis and policy options - Torsten Niechoj; Till van Treeck (Intervention. European Journal of Economics and Economic Policies, 2010)
First paragraph: The financial market crisis that transformed into a global recession is a challenge for both economic theory and policy. In retrospect, nearly three years after the first signs of the crisis, a few tentative conclusions concerning the appropriateness and effectiveness of the responses to the crisis might be possible. After an initial state of shock, the political system acted forcefully and issued programmes to stabilise both financial sector and the real economy all over the world. Moreover, governments started to talk about an encompassing regulation of the financial sector, which was supported by many economists. This is indeed remarkable compared to what used to be common sense in the years before within advisory bodies – among others the European Commission, the IMF and academic think tanks. Privatisation and liberalisation of markets were, then, thought to be key to increasing the capacity of the economy to absorb shocks and to guarantee high growth rates and economic well-being. Although in that respect politicians and economists obviously did learn from the crisis and began to take seriously alternative ideas which had for a long time been absent in the debates, a return to normality is already imminent; the planned fiscal retrenchment programmes, particularly within the European Union, and the deferral of regulatory measures for financial markets are testament to this. The king is dead, long live the king? From today's view it is not clear whether or not, in the longer run, this crisis has really shaken the foundations of economic thinking and policy making.
Keywords: 330